The effects of emotion and COVID-19 context priming on the size and color of drawings: based on human figure drawings and tree drawings - Cao, Huijing; Zhang, Xiaohan; Zhang, Xinlei; Yan, Wenhua (Frontiers in Psychology, 2023)
This study aimed to investigate the effects of emotional themes and the COVID-19 pandemic context priming on the size and colour of drawings. A 3 (emotion: peacefulness, gratitude, loneliness) × 2 (context: pandemic, regular) mixed design was used and 113 university students in Shanghai were recruited to draw human figures and trees using 10 marker colours. Results found that the size of the drawings depicting loneliness was smaller than that of the those depicting peacefulness and gratitude. Drawings depicting loneliness used more cool and non-preferred colours; drawings depicting gratitude used more warm and preferred colours. Drawings in the pandemic context were larger, which may reflect the more significant threat perceived by individuals. Drawings in the pandemic context used more red colours, showing symbolic meanings such as danger.